Economic Migration, Networks and Human Capital Transferability from the New European Borderlands. A Comparison of Five Eastern European Countries. - Alexander M. Danzer; Barbara Dietz (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2008)
In the paper we use a unique new data set which has been collected in late 2006 in Armenia, Belarus, Georgia, Moldova and Ukraine to investigate the determinants for short term migration and its destination and duration patterns. Special attention is paid to the role played by personal networks to Eastern and Western destinations as well as investments into the transferability of human capital made by migrants prior to their stay abroad. We find that many determinants and migration patterns are quite similar across the CIS countries under consideration but exhibit some surprising differences to standard results from the migration literature, e.g. the prevalence of older migrants and the low importance of children in the migration decision process. Networks and human capital transferability are the main explaining factors for the migration and destination decision, a result proofing robust after correcting for endogeneity. We expect that migration is likely to grow in importance for some countries at the European Borderlands, as networks develop and the costs of migration decrease. However, our analysis reveals that fears of brain drain have little substance as the educational background of migrants is rather low. As a considerable number of migrants have invested into destination country specific human capital prior to migration, this improved human capital endowment can benefit both, migrants and the society of sending countries, alike.
Keywords: 330; Migration; human capital transferability; migration networks; cross-country study